Manajemen Pembiayaan Pendidikan dalam Meningkatkan Mutu Pendidikan di Madrasah Aliyah Imam Muslim Serdang Bedagai - Mesiono Mesiono; Suswanto Suswanto; Rahmat Rifai Lubis; Haidir Haidir (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
This study aims to determine the management of education financing in relation to efforts to improve the quality of education. This research is focused on the managerial head of the Aliyah Imam Muslim madrasah, Serdang Bedagai Regency. This research uses qualitative methods based on descriptive studies. Data collection techniques using observation, interviews, and documentation studies. Data analysis was performed using the Miles and Huberman model stages, namely data reduction, data presentation, and conclusion drawing. The data validity test used triangulation and member crosscheck. The results showed that the management of education financing at Madrasah Aliyah Imam Muslim Serdang Bedagai Regency has a family principle, is effective, efficient, productive, transparent and can be accounted for in accordance with existing procedures, namely the upward hierarchical pattern to the Chairman of the Foundation. In improving the quality of education, the principal is in charge of managing education as best as possible and reporting the draft budget for school financing is given to the Head of the Foundation, the head of madrasah also has the task of how to improve the quality of education in Madrasahs by coordinating every activity with peers in order to realize the quality of education through education financing management